Colloidal Clusters of Bimetallic Core–Shell Nanoparticles for Enhanced Sensing of Hydrogen in Aqueous Solution. (19th January 2018) - Wy, Younghyun; Lee, Seunghoon; Wi, Dae Han; Han, Sang Woo
Abstract: Developing sensitive and stable hydrogen sensors is of great importance for sustainable energy development. Here, a novel hydrogen sensing platform is described based on colloidal clusters of Au@Pd core–shell nanoparticles (Au@Pd NPCs) with characteristic localized surface plasmon resonance (LSPR) properties. Au@Pd NPCs with well‐controlled topologies exhibit highly pronounced sensitivity for LSPR‐based hydrogen sensing in aqueous solution in comparison to their nanoparticle counterparts and previously reported Au–Pd bimetallic nanostructures, which can be attributed to highly promoted plasmonic field resulting from the cluster formation. Furthermore, Au@Pd NPCs show stable sensing capability for repeated hydrogen sensing cycles. The present strategy for devising high‐performance LSPR‐based hydrogen sensors via the controlled assembly of bimetallic nanoparticles can be applied to the development of efficient plasmonic platforms for various sensing applications. Abstract : Colloidal clusters of core–shell nanoparticles consisting of plasmonic Au cores and Pd shells with controlled topologies exhibit pronounced sensitivity for localized surface plasmon resonance‐based hydrogen sensing in aqueous solution due to a highly promoted plasmonic field, resulting from the cluster formation of Au@Pd bimetallic nanoparticles.